2001
DOI: 10.1080/09575140120057167
|View full text |Cite
|
Sign up to set email alerts
|

Passion, Paradox and Professionalism in Early Years Education

Abstract: Early Years practitioners frequently use words like 'passionate' to describe themselves and their attitudes to working and playing with young children. But how is this emotive and emotional word to be interpreted by others? Given any evidence of real political in uence or strength, this mainly female workforce cannot perhaps be said to be suf ciently passionate or forceful in justifying and promoting their beliefs and ideologies. Herein lies one of many paradoxes in early childhood: it seems impossible to work… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
47
0
3

Year Published

2011
2011
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(51 citation statements)
references
References 9 publications
(9 reference statements)
1
47
0
3
Order By: Relevance
“…(525) Her account seems to accurately describe the position of the ECEC workforce. The currently still dominant version of ECEC professionalism which emanated from Labour government policy has been criticised for imposing a centrally defined agenda which is deeply inscribed by performativity and managerialism (Moyles 2001;Osgood 2006;Urban 2008). Moss (2006) for example argues that autonomy in the workplace for all ECEC practitioners has been much reduced by the introduction of EYFS curriculum framework and the regulatory regime of which it is part, to the extent that the carer is repositioned as a 'technician'.…”
Section: Professionals Professionalism and Ecec Reviewedmentioning
confidence: 98%
“…(525) Her account seems to accurately describe the position of the ECEC workforce. The currently still dominant version of ECEC professionalism which emanated from Labour government policy has been criticised for imposing a centrally defined agenda which is deeply inscribed by performativity and managerialism (Moyles 2001;Osgood 2006;Urban 2008). Moss (2006) for example argues that autonomy in the workplace for all ECEC practitioners has been much reduced by the introduction of EYFS curriculum framework and the regulatory regime of which it is part, to the extent that the carer is repositioned as a 'technician'.…”
Section: Professionals Professionalism and Ecec Reviewedmentioning
confidence: 98%
“…Bagdi and Vacca 2005;Moyles 2001) have drawn from their studies with early years practitioners as they suggest that early years work demands strong feelings towards supporting children.…”
Section: Advantages Of Field Experiencementioning
confidence: 98%
“…Other research with practitioners has identified that they describe their role in terms of a feel and an ethos (Cottle and Alexander 2012) and an ethic of care (Osgood 2006). There has been a long-standing emphasis on the importance of a caring disposition and the capacity for emotional commitment, often referred to as 'passion', when working with children (Moyles 2001;Osgood 2010). In the context of professional development for initial and continuing members of the early years workforce, there is a risk of assuming that, if people have found their way on to an early childhood course, they very likely already have certain general dispositions, inherent and enduring qualities of mind and character that mean they are well suited to the early years workforce.…”
Section: Qualifications In the Early Years Sectormentioning
confidence: 99%